Correlation of Blood Glucose, Creatinine, and Uric Acid with Blood Pressure in Hypertension Patients : Korelasi Glukosa Darah, Kreatinin, dan Asam Urat dengan Tekanan Darah Pada Pasien Hipertensi - Faustine, Ingrid; Yuliet, Yuliet; Hardani, Ririen; Hamdani, Silviana; Alfia, Dhara; Susilawati, Ni Made; Adisaputra, Arya Dibyo (Jurnal Farmasi Galenika (Galenika Journal of Pharmacy) (e-Journal), 2025)
Poorly controlled hypertension in hypertensive patients can increase the risk of cardiovascular disease in the future. Some of the triggering factors are impaired kidney function which is characterized by an increase in creatinine levels and other factors as well, namely an increase in uric acid levels and an increase in blood sugar levels. This study aims to analyze the correlation between blood glucose, creatinine, and uric acid levels in hypertensive patients in Central Sulawesi. With a cross-sectional design, this observational study involved 50 adult hypertensive patients in health facilities. Data were taken from laboratory examination results during visits and analyzed descriptively and analytically. The results showed that 60% of hypertensive patients were female, 62% had a family history of hypertension, and 80% still had blood pressure that was included in the criteria for hypertension. As many as 34% of hypertensive patients had abnormal blood glucose levels, 32% had abnormal creatinine levels, and 26% had abnormal uric acid levels. Still, no relationship was found between the three with blood pressure (p> 0.05). The correlation between blood glucose and blood pressure was -0.221, creatinine and blood pressure was -0.112, and uric acid and blood pressure was 0.132. It can be concluded that there is a positive correlation with a very weak correlation strength between uric acid levels and blood pressure in hypertensive patients.